2017
DOI: 10.1186/s10152-017-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of epilithic diatoms along climatic, spatial and physicochemical variables in the Baltic Sea

Abstract: The species richness and community composition of the diatom communities were studied in the Baltic Sea, Northern Europe, to enhance knowledge about the diversity of these organisms in a brackish water ecosystem. Many organisms in the Baltic Sea have been studied extensively, but studies investigating littoral diatoms are scarce. The goal of this study was to examine the importance of climatic, spatial and water physicochemical variables as drivers of epilithic diatoms in the Gulf of Finland and the Gulf of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The initial similarity (IS) refers to the dissimilarity index value at a spatial distance of 1 m. Shown is also the coefficient of correlation between environmental and spatial distance (distance r) in each month. The statistical significance of the variables is based on the p value: *p < 0.05, **p < 0.01, ***p < 0.001 2012; Bottin et al 2014;Virta and Soininen 2017). Both environmental and spatial distances were related with community similarities in each month also here even when the other variable group was controlled for.…”
Section: Distance Decay Of Community Similaritymentioning
confidence: 99%
“…The initial similarity (IS) refers to the dissimilarity index value at a spatial distance of 1 m. Shown is also the coefficient of correlation between environmental and spatial distance (distance r) in each month. The statistical significance of the variables is based on the p value: *p < 0.05, **p < 0.01, ***p < 0.001 2012; Bottin et al 2014;Virta and Soininen 2017). Both environmental and spatial distances were related with community similarities in each month also here even when the other variable group was controlled for.…”
Section: Distance Decay Of Community Similaritymentioning
confidence: 99%
“…grazing pressure) covarying with pool distance to the sea. The secondary importance of local environmental variables on diatom richness disagrees with Virta and Soininen ( 2017 ), who found that diatom richness in the Baltic Sea was best explained by pH and nutrients. In contrast to diatoms, variation in both cyanobacteria and non-cyanobacteria richness across the pools was most strongly related to TP, agreeing with earlier studies on the importance of nutrient availability on bacterial richness (Wang et al .…”
Section: Discussionmentioning
confidence: 64%
“…Navicula perminuta and T. fasciculata have been found to occur along a wide salinity range, with increasing relative abundances towards higher salinities also in the Baltic Sea area (Ulanova, Busse and Snoeijs 2009 ). Likewise, D. moniliformis has an apparently wide salinity tolerance as it is common in the Baltic Sea (Virta and Soininen 2017 ), but also found in freshwater ecosystems with elevated conductivity (Krammer and Lange-Bertalot 1991a ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, investigations of factors and regularities of distribution of b sity of organisms at different levels of organization became especially relevant Such investigations are not only of ecological but also evolutionary importan Geographical, physicochemical, climatic and historical factors may be the most im for the distribution of protists [34,[36][37][38]. The majority of these investigations dea the analysis of biotopes either within one continent [36,37] or within one wate [34,38].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, investigations of factors and regularities of distribution of b sity of organisms at different levels of organization became especially relevant Such investigations are not only of ecological but also evolutionary importan Geographical, physicochemical, climatic and historical factors may be the most im for the distribution of protists [34,[36][37][38]. The majority of these investigations dea the analysis of biotopes either within one continent [36,37] or within one wate [34,38]. Although there are few studies studies on intercontinental factors and r In recent years, investigations of factors and regularities of distribution of biodiversity of organisms at different levels of organization became especially relevant [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%